Development of a drug discovery protocol through the expression of key mycothiol biosynthetic enzymes for Mycobacterium tuberculosis - Lamprecht, Dirk Antonie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2008.